Inhibitory Effect of Isolated Bacteria from the Phycosphere of Levanderina fissa on the Growth of Different Microalgae - Tang, Yali; Xie, Changliang; Jin, Xiaotong; Wang, Zhaohui; Hu, Ren (Frontiers in Marine Science, 2022)
Levanderina fissa (formerly Gyrodinium instriatum) frequently caused blooms in the Pearl River Estuary and it had few advantages in the interspecific competition with other bloom-forming algal species. The phycosphere bacteria, which closely interact with the algal cells, may play an ecological function role in its population dynamics and bloom occurence. To test the hypothesis, we isolated and identified cultivable bacteria coexisting in different growth stages of L. fissa by gradient dilution method and investigated the characteristics of the bacterial interactions with three diatom species (Chaetoceros curvisetus, Skeletonema dohrnii, and Phaeodactylum tricornutum) and three dinoflagellate species (Scrippsiella acuminata, Karenia mikimotoi and the host algae). One of the isolated bacterial strain Lf7, identified as Alteromonas macleodii phylogenetically, showed significant inhibitory effects on different algal species except its host. Meanwhile, all algal species, especially its host showed significant stimulatory effects on bacteria Lf7 growth. These results indicate that phycosphere bacteria Lf7 may have some ecological roles in the competition between its host algal L. fissa and other phytoplankton. The study highlights the complicated interactions between phycosphere bacteria and their host algae, hinting an indirect way of mutualism associations which needs further studies.